2013
DOI: 10.3384/lic.diva-98656
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Energy Awareness in Mobile Communication

Abstract: Although evolving mobile technologies bring millions of users closer to the vision of information anywhere-anytime, device battery depletions hamper the quality of experience to a great extent. The massive explosion of mobile applications with the ensuing data exchange over the cellular infrastructure is not only a blessing to the mobile user, but also has a price in terms of rapid discharge of the device battery. Wireless communication is a large contributor to the energy consumption. Thus, the current call f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…A previous study [15] reveals 5 famous instant messenger bandwidth utilization inefficiencies in conversion and background receiving messages. A previous study [16] investigated data collected from IM 51 users" single chat (one to one) text messages. IM end user typed multiple messages and bundled together to user end typing to reduce the energy cost of transmission packets.…”
Section: Related Workmentioning
confidence: 99%
“…A previous study [15] reveals 5 famous instant messenger bandwidth utilization inefficiencies in conversion and background receiving messages. A previous study [16] investigated data collected from IM 51 users" single chat (one to one) text messages. IM end user typed multiple messages and bundled together to user end typing to reduce the energy cost of transmission packets.…”
Section: Related Workmentioning
confidence: 99%
“…A previous study reveals 5 famous instant messenger bandwidth utilization inefficiencies in conversion and background receiving messages [34]. A previous study [35] investigated data collected from IM 51 users single chat (one to one) text messages. IM end user typed multiple messages and bundled together to user end typing to reduce the energy cost of transmission packets.…”
Section: Related Workmentioning
confidence: 99%
“…High-level protocols over cellular network also have an impact on overall energy requirements of a system [14]. A review of various middleware protocols for telemetry applications can be found in [15].…”
Section: Related Workmentioning
confidence: 99%